Peranan Mahasiswa KKN UNIWARA Dalam Melaksanakan Program Kegiatan Pengabdian Kepada Masyarakat Di Kelurahan Tapaan Kota Pasuruan - M. Hengki Riawan P; M. Naufal Syarif; Najma Jahira; Siti Khodijah; Rismatul Mukminin (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2023)
Real Work Lectures (KKN) are a means of application in the development of science and technology, which are carried out outside the university campus within certain time limits, work methods and requirements. The community service offered at the undergraduate level is an effort to increase the content and quality of education for students and to achieve added value in higher education. With the implementation of this community service program, it is hoped that it can develop the role of students in improving their social skills and personality. The purpose of this research is to reveal the role of field studies in developing students' skills. The population and sample of this study were students who participated in the KKN and the community around where the students were held. Data collection methods used are interviews, observation and documentation. This interview method aims to gather information about the social conditions of the community and the potential that exists in the Tapaan Village. From the research results, it was found that the role of KKN is part of developing student competencies as a form of service to the community, especially in Tapaan Village.